APLICAÇÃO DE PROCESSOS OXIDATIVOS E ELETROQUÍMICOS AVANÇADOS E AVALIAÇÃO DE UMA PLANTA FOTOELETROQUÍMICA SOLAR NO TRATAMENTO DE ÁGUA CINZA - Paulo Renato dos Santos (2023)
Water generated waste is a global problem today. Conventional biological treatments are of low efficiency, involving toxic and resistant (recalcitrant) effluents. In this context, we cite light gray water, which is gray wastewater defined as wastewater from bathrooms, washbasins, kitchen sinks, washing machines and tanks, in houses, buildings, schools, among others. Advanced oxidative processes have proven to be an effective strategy, from an environmental, technical and economic point of view, for the treatment of these effluents, increasing the degradation efficiency. The objective of this work is to use a 2k factorial design with a central point to evaluate the degradation and mineralization of surfactants present in light gray water and toxicity through the techniques of anodic oxidation (AO-H2O2) photo electro Fenton (PEF) and O3/H2O2. The scale up in a pilot solar plant was also evaluated using the Photoelectro-Fenton solar technique (PEFS). The feasibility of applying factorial design to the treatment of light gray water containing dodecyl-benzene sulfonic acid (LAS) by electrochemical processes of advanced oxidation in Na2SO4 electrolyte on a bench scale was demonstrated. The anodic oxidation processes with hydrogen peroxide electrogeneration and Photoelectro-Fenton (PEF) were studied by factorial design of 23 with insertion of the central point, using a first-order mathematical polynomial. On AO-H2O2 using a thin-film boron-doped diamond anode and an air-diffusion carbon-PTFE cathode (both 3 cm2 area) achieving 76% degradation with 40 mg L-1 LAS and NPOC removal of 52.4% with under optimized conditions. For PEF using [Fe2+] = 5 mg L-1 and current density j = 77.5 mA cm-2 the best responses for LAS degradation were 63.12% and 78.28% NPOC removal. The optimal conditions found in the treatment of PEF by factorial design were used in the treatment of 10 L of ACc by solar Photoelectro-Fenton process (SPEF) in a composite parabolic collector solar reactor (CPC) equipped with an electrochemical cell-type filter press, reaching 70% of LAS removal and 55% of ACc mineralization after 240 min of treatment. As for the treatment with ozonation with the addition of hydrogen peroxide, the influence of the independent variables was evaluated: ozone concentration, hydrogen peroxide concentration, pH and time in degradation, mineralization and acute toxicity for Artemia Salina in the treatment of light gray water performing a 24 factorial design with triplicate at the central point, totaling 19 experiments, using Minitab software version 19. The responses of the factorial design of the O3/H2O2 process showed linear behavior with excellent linear regression coefficients R2 = 96.97% and R2adj = 94 .54% for degradation and R2 = 95.36% and R2adj = 91.65% for mineralization showing a low experimental error. The time variable had a greater effect on the degradation response and the pH variable had a greater effect on mineralization. For a time of 60 min, it obtained a degradation of 82.20% with an ozone concentration of 44 mg L-1 and 10 mg L-1 of hydrogen peroxide concentration, whereas for mineralization it was with an ozone concentration of 16 mg L-1 and 50 mg L-1 of hydrogen peroxide concentration, reaching after 60 minutes 53.73% of mineralization. The tests with Artemia Salina were carried out under the best conditions of the experiments, and the processes with ozonation and PEF proved to be very effective, not showing acute toxicity. These two processes are promising in the application of new technologies for surfactant removal.